Estudo do processo de calcinação do caulim para produção de geopolímeros - BOTELHO, Jhonata Albuquerque (2024)
Portland cement is one of the most widely used materials in the world and is responsible for around 7.5% of annual greenhouse gas emissions. Engineers and scientists aiming to reduce further damage to the environment are researching and designing high-performance alternative cements using green technology to replace Portland cement. Among the class of alternative cements are geopolymers, inorganic polymers developed by French scientist Joseph Davidovits. Geopolymers are produced by combining a source of amorphous aluminosilicates with an alkaline solution, which through geopolymerization forms a highly durable, refractory and mechanically resistant material due to the Si-O-Al bonds. Metakaolin is one of the main precursor materials for aluminosilicates for the production of geopolymers due to its chemical composition and reactivity. In this study, the mechanical performance of geopolymers based on metakaolin from the Amazon region with partial addition of blast furnace slag was investigated, based on three calcination temperatures, 700°C, 800°C and 900°C, for 2h each. Initially, calcination was carried out to obtain metakaolin at the three temperatures, then the physical properties of loss on ignition and moisture content, and mineralogical properties were determined through X-ray diffractometry. Then, geopolymer paste specimens were produced from each metakaolin obtained, with 10% partial addition of blast furnace slag and a 10 Mol/L alkaline solution, to determine compressive strength. Then, the fractured geopolymer cements were analyzed by optical microscopy. The metakaolin obtained at the three temperatures presented physical properties consistent with the literature. The X-ray diffraction analysis showed an amorphous halo with a sharp silica peak, which resulted in a compressive strength of 44, 45, 38 MPa, from the temperature variations of metakaolin production 700, 800, and 900°C, respectively. Regarding the morphological analysis, the pastes produced with metakaolin obtained at 700° and 800° presented a dense and homogeneous surface, when compared to the geopolymer paste produced with metakaolin obtained at 900°C, due to the low pozzolanic activity when it compared with others thermic variations.